DNA Evidence: Examining Police Officers’ Knowledge of Handling Procedures in a Mid-Size Department - Hauhart, Robert C.; Menius, Kimberly R. (International Journal of Criminology and Sociology, 2014)
Studies of policing dominate the criminal justice literature but very few studies report empirical data regarding police handling of evidence, specifically including DNA evidence. Given that evidence handling is crucial in the investigation and prosecution of criminal offenders, this gap in the literature is surprising. The present paper addresses the quality of evidence handling in a mid-size police department in the northwest United States. Three surveys - two of officers within the department and one of state crime lab managers who test and examine evidence samples provided to them by local police departments - suggest that police offers in this mid-size city are only modestly familiar with proper evidence handling procedures, including those procedures regarding the collection, packaging, transportation and submission of possible DNA evidence.